Strategic problem-solving: A state of the art - Fernandes, A.; Pereira, L.; Dias, Á.; Gupta, V. (IEEE Engineering Management Review, 2023)
Strategic problem-solving is a relevant skill in business, widely used to identify problems and find inherent solutions to stop, avoid, or mitigate such problems. The literature revolving around problem-solving has been enriched over the years with several theories and approaches. Problem-solving is critical in helping maintain a successful business and looking at problems as objectively and modestly as possible. This systematic literature review aims to summarize the current state of the art on the topic of strategic problem-solving. To this end, a bibliometric analysis based on data retrieved from the Web of Science database is performed, and results are reported in this article. The analysis allowed us to identify five different clusters on the theme of problem-solving, namely, product development and open innovation, organization and firm-customer relationship, creative process and resilience, learning, skills, and work environment, and partnership negotiation/cooperation and the role of supply chain and quality management. These clusters are distinct yet complementary to each other, a trait that was possible to observe when common top papers from each cluster were selected for further discussion. Finally, a shift in the topics of research from past to present was observed which might be related to the emergence of new theories and the turnover of authors. The growing number of recent publications reveals the value of this article and suggests that problem-solving will always have room for improvement.